Long Non-coding RNA 332443 Inhibits Preadipocyte Differentiation by Targeting Runx1 and p38-MAPK and ERK1/2-MAPK Signaling Pathways - Xiao, Fen; Tang, Chen-Yi; Tang, Hao-Neng; Wu, Hui-Xuan; Hu, Nan; Li, Long; Zhou, Hou-De (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) have emerged as integral regulators of pathophysiological processes, but their specific roles and mechanisms in adipose tissue development remain largely unknown. Here, through microarray analysis, co-expression, and tissue specific analysis of adipocyte tissues after fasting for 72 h, we found that Lnc-FR332443 expression was dramatically decreased, as well as the expression of Runx1. The UCSC database and Ensembl database indicated that Lnc-FR332443 is the antisense lncRNA of Runx1. Lnc-FR332443 and Runx1 are highly enriched in adipose tissue and downregulated during adipogenic differentiation. Adipose tissue-specific knockdown of Lnc-FR332443 increased fat mass in vivo, and specific knockdown of Lnc-FR332443 in 3T3-L1 preadipocytes promoted adipogenic differentiation. In this process, Runx1 expression was decreased when Lnc-FR332443 was downregulated in adipocytes or 3T3-L1 preadipocytes, and vice versa, when Lnc-FR332443 was upregulated, the expression of Runx1 was increased. However, overexpression of Runx1 decreased the expression of the adipocyte cell marker genes PPARγ, C/EBPα and FABP4 significantly, while not affected the expression of Lnc-FR332443. Mechanistically, Lnc-FR332443 positively regulates Runx1 expression in mouse adipocytes and suppresses adipocyte differentiation by attenuating the phosphorylation of MAPK-p38 and MAPK-ERK1/2 expression. Thus, this study indicated that Lnc-FR332443 inhibits adipogenesis and which might be a drug target for the prevention and treatment of obesity.